The princess saves herself in this one - Lovelace, Amanda (Andrews McMeel Publishing, a division of Andrews McMeel Universal, 2017)
"From Amanda Lovelace, a poetry collection in four parts: the princess, the damsel, the queen, and you. The first three sections piece together the life of the author while the final section serves as a note to the reader. This moving book explores love, loss, grief, healing, empowerment, and inspiration."--Publisher's website.